LEGAL PROTECTION FOR CONSUMERS OF E-2B BANDA ACEH REFILL DRINKING WATER DEPOT IN TERMS OF INDONESIAN POSITIVE LAW AND ISLAMIC LAW - Muhammad Arief; Agustin Hanapi; Nilam Sari (JURISTA: Jurnal Hukum dan Keadilan, 2024)
Article 1 of Law No. 8 of 1999 which regulates "Consumer protection law", in Article 1 states "Consumer protection as all efforts that ensure legal certainty to provide protection to consumers". The researcher applies empirical law in this study, which is legal research that examines the adoption or application of normative legal provisions in each unique legal event in society. Various data sources were used, including secondary data from a literature review as well as primary data from interviews with business owners. The research findings show that the E-2B Banda Aceh refillable drinking water depot business has taken steps to protect consumers by obtaining SLHS in accordance with Permenkes No. 492 of 2010. With the SLHS, the business has met good sanitation and hygiene standards in processing and distributing drinking water that is free from bacteria as required by the Ministry of Health based on Permenkes No. 492 of 2010. The principles of fairness, integrity, and accountability are the basis of consumer protection in Islamic law.